A clinically managed weight loss program evaluation and the impact of COVID-19 - Cachero, Katrina; Mollard, Rebecca; Myrie, Semone; MacKay, Dylan (Frontiers in Nutrition, 2023)
Introduction With the prevalence of obesity increasing, many weight-loss programs were created to aid in combating the trend. The Weight Loss Clinic (WLC) was created to provide personalized support for lifestyle changes using a multidisciplinary team with medical oversight. This study evaluated the clinically-managed weight loss program at the Wellness Institute. Methods This was a prospective evaluation of a newly established program between January 2019–August 2020. Participants who entered the weight loss program were approached to learn about the evaluation. A total of 41 participants were included. The primary outcomes included changes in body weight and achievement of more than 5% initial body weight loss. Outcome measures were collected pre-and post-program and the data was analyzed through paired t-tests on R studio. Results Greater body weight-loss was seen in completers pre-COVID-19 compared to those who completed during the pandemic (Mean, ±SD; 7.51 ± 6.24 kg n = 13 p < 0.001 vs. 1.75 ± 4.43 kg n = 9, p = 0.02). Completers pre-COVID-19 demonstrated improvements in waist circumference, Framingham risk score, blood pressure, hemoglobin A1C, and body fat percentage. Conclusions and implications Though the sample size was small to show definitve evidence, the results may suggest the program worked well prior to the pandemic but the pandemic created barriers to weight-loss for participants.